Metode Bermain Gerak Dan Lagu Untuk Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Nurainiyah; Novita Widiyaningrum (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Playing is the most fun thing for children. Therefore, teachers must be creative and innovative in developing methods of learning to play that are fun for children. Teachers must understand the character of the children they teach. That way the learning objectives will be achieved optimally. The method of playing motion and songs, one of which can be an alternative for teachers to improve children's social emotional development. The research method used in this study is a type of qualitative research with a descriptive approach. The data collection techniques used were participant observation, in-depth interviews and documentation. And the data analysis uses the triangulation technique method, which combines data obtained from observation, interviews and documentation methods. fast tempo and varied movements. So that the scope of children's social emotional development which includes self-awareness, a sense of responsibility towards themselves and others as well as prosocial behavior of children can